Iron phosphate materials as cathodes for lithium batteries the use of environmentally friendly iron in lithium batteries - Prosini, Pier Paolo (Springer, 2011)
Iron Phosphate Materials as Cathodes for Lithium Batteries describes the synthesis and the chemical?physical characteristics of iron phosphates, and presents methods of making LiFePO4 a suitable cathode material for lithium-ion batteries. The author studies carbon?s ability to increase conductivity and to decrease material grain size, as well as investigating the electrochemical behaviour of the materials obtained. Iron Phosphate Materials as Cathodes for Lithium Batteries also proposes a model to explain lithium insertion/extraction in LiFePO4 and to predict voltage profiles at various discharge rates. Iron Phosphate Materials as Cathodes for Lithium Batteries is written for postgraduate students and researchers in electrochemistry, R&D professionals and experts in electrochemical storage.